Effects of the Getting Ready for School intervention on children's school readiness skills - Marti-Castaner, Maria; Merz, Emily C.; Wiltshire, Cynthia A.; Melvin, Samantha A.; Henry, Kimberly; Landers, Cassie; Noble, Kimberly G.; Duch, Helena (Frontiers in Developmental Psychology, 2024)
IntroductionSkill-based curricula supplementing Head Start programming have shown great promise as early interventions improving school readiness of children from socioeconomically under-resourced families. The Getting Ready for School (GRS) intervention builds on such research by providing a supplemental skill-based curriculum targeting three core school readiness domains—language/literacy, math, and self-regulation—using learning activities aligned across the classroom and home contexts. The goal of this study was to examine the effects of the GRS intervention on school readiness skills in children in Head Start programs.MethodsParticipants were 3- to 4-year-olds (N = 463, 46% male, 81% Hispanic/Latine). Classrooms were non-randomly assigned to the GRS intervention (n = 20) or Head-Start-as-usual comparison group (n = 17). At pretest and posttest, children completed assessments of early language/literacy, math, and self-regulation. Multilevel modeling was used to examine the group-by-time interaction in prediction of children's school readiness skills.ResultsSignificant group-by-time interactions were found for early language/literacy (vocabulary, print knowledge) and math skills. Children in the intervention group demonstrated significantly greater gains over time in these skills compared to children in the comparison group. At posttest, children in the intervention group had significantly higher vocabulary than children in the comparison group (effect size = 0.34). Intervention effects were not found for self-regulation.DiscussionThe GRS intervention may support early language/literacy and math skills in preschool children from socioeconomically under-resourced families. Future studies focused on a modified version of the intervention could demonstrate larger effect sizes and improvements in self-regulation.